Immunotherapy Is Evolving and Promising for Lung Cancer - Boltz, Kathy (MD Conference Express, 2015)
Checkpoint inhibitors have clear evidence of activity against programmed cell death and programmed death ligand in non–small cell lung cancer. Immunotherapies are increasingly being investigated in combinations, though strong immune responses warrant caution. Current therapeutic vaccines have had limited success in lung cancer. Clinical trial strategies are developing to best test targeted therapies.